Puffball spores improve wound healing in a diabetic rat model - He, Tangtang; Sun, Pengfei; Liu, Bo; Wan, Shiwei; Fang, Penghua; Chen, Jun; Huang, Guicheng; Min, Wen (Frontiers in Endocrinology, 2022)
Persistent chronic oxidative stress is primary pathogenic characteristics of diabetic foot ulcers. Puffball spores are traditional Chinese medicine used to treat diabetic foot ulcers infections and bedsores. However, its role and mechanism of action in diabetic wounds remain largely unknown. This study explored the effectiveness of puffball spores in diabetic wound treatment and the underlying mechanisms. Puffball spores were applied to streptozotocin (STZ)-induced diabetic Sprague-Dawley rats to observe the accelerated wound healing.Real-time quantitative PCR, Western blot, hematoxylin-eosin and Masson's trichrome staining, immunohistochemistry and immunofluorescence assays were performed. As indicated by wound and serum histology and biochemical analyses, puffball spores accelerated wound healing by activating Akt/Nrf2 and its downstream antioxidant gene expression, providing enormous antioxidant activity, promoted angiogenesis, collagen deposition. This study showed that puffball spores could accelerate diabetic wound healing, increase antioxidant capacity, promote the expression level of vascular markers, and suppress inflammation, providing a theoretical basis for treatment of diabetes and refractory wounds.